Effect of crop residues and root exudates on mycelial growth, sclerotial formation, and Sclerotium rolfsii-induced stem rot disease of groundnut - N.B. BAGWAN, VINOD KUMAR*, A.L. RATHNAKUMAR and (Indian Phytopathology, 2012)
The effect of aqueous leaf extracts, dried crop residues and root exudates of rotational crops commonly grown in groundnut production system viz., sorghum, pearl millet, maize, wheat, cotton, castor, sesame, sunflower, safflower, mustard, soybean, pigeon pea, green gram, black gram, chick pea, cow pea, pea, garlic and onion on mycelial growth, sclerotial germination, number and size of sclerotia of Sclerotium rolfsii Sacc. and the incidence of stem rot in groundnut (Arachis hypogaea L.) caused by this pathogen were studied under in vitro conditions. Aqueous leaf extracts (ALE) (100 g/100 ml water) of garlic, onion, pearl millet, sunflower and sorghum at 5% concentration reduced mycelial growth and completely inhibited sclerotia formation. ALE of pigeon pea, green gram, and black gram moderately reduced mycelial growth but there was sclerotial formation. ALE of groundnut and soybean enhanced mycelial growth, size and number of sclerotia. The lowest germination of sclerotia was on crop residue of sunflower and garlic whereas the highest was on the crop residue of soybean and groundnut. In the pot experiment, the lowest incidence of stem rot was observed in sunflower and garlic crop residue, and the highest was in soybean followed by groundnut crop residue. Significant but varied level of inhibitory effect of root exudates of twelve crops viz., sorghum, pearl millet, maize, wheat, garlic, onion, sesame, sunflower, safflower, mustard, cotton and castor on mycelial growth of S. rolfsii and reduction in germination of sclerotia was observed. The results of this study will be useful in deciding the rotational crops in the integrated disease management of groundnut.